Investigation the temperature-dependent surface mechanical properties of PolyJet printed samples by cyclic indentation testing in a DMA system - Luca Kotrocz; Péter Bakonyi (Results in Materials, 2023)
Tools and products used in everyday life are regularly exposed to dynamic, cyclical stress. These stresses are particularly significant in the case of polymers, as their viscoelastic behavior means that creep can be considerable even at room temperature. Therefore, polymer components are often tested for maximum deformation rather than for maximum load-bearing capacity. Basic material testing methods are tensile, compression, and flexure tests, which are excellent for determining the material properties of the bulk material. However, in some cases, it is more appropriate to investigate surface mechanical properties. The ideal method for this is the depth-sensing indentation test. This method has been widely applied to polymers in the last ten years, but cyclic tests are rare, and creep is not considered in this type of indentation test. In the case of cyclical tests, temperature dependence is not fully examined, either. This paper presents the results of cyclic indentation tests on photopolymer specimens produced by additive manufacturing with the use of a dynamic mechanical analyzer with a unique indentation clamp. We performed the tests at three temperatures to investigate the influence of temperature on cyclic indentation tests. The test results show the variation of deformation between cycles and the significant effect of temperature.